Technological innovation of Continuous Glucose Monitoring (CGM) as a tool for commercial aviation pilots with insulin-treated diabetes and stakeholders/regulators: A new chance to improve the directives? - Strollo, F.; Furia, A.; Verde, P.; Bellia, A.; Grussu, M.; Mambro, A.; Petrelli, M.D.; Gentile, S. (Diabetes research and clinical practice, 2021)
Civil aviation pilots who develop insulin-treated diabetes and want to renew a Commercial Pilot License (CPL) represent a medical, social and regulatory problem. This depends on justified concerns about hypoglycemia, the most threatening event for people who carry out jobs requiring a high level of concentration and reliability. This negatively affects social and working aspects of pilots’ lives, who have a high profile and a high-cost professional qualification. It could be possible now to revise this attitude thanks to the availability of Continuous Glucose Monitoring (CGM) devices. CGM clearly showed to prevent hypoglycemic events in insulin-treated diabetic patients by allowing strict monitoring and trend prediction of glucose levels. By systematizing available data on such devices and present regulations in CPL issuance worldwide, our review can be used as handy tool for a fruitful discussion among the scientific community, national and international civil aviation regulators, stakeholders and pilots, aimed at evaluating the evidence-based opportunity to revise CPL issuance criteria for insulin-treated diabetic pilots. For the above-mentioned reasons, there are, among the regulatory administrations of Civil Aviation around the globe, several different approaches and limitations set for the subjects with insulin-treated diabetes who want to obtain, or renew, a CPL.